Implementation of Dart Programming Language in Mobile-Based DRs Snack Sales Application Design - Vindua, Raditia; Handayani, Dede; Ekrinifda, Ardilla (Information Technology and Science (ITScience), 2024)
DRs Snack has been making and selling snacks in the vicinity. However, they face problems in manually recording sales and generating accurate reports. Therefore, this project aims to design and implement a mobile-based sales system application that will help DRs Snack in managing sales and recording reports more efficiently. The main objective of this project is to design and develop a mobile-based sales system application with Dart programming language and Flutter framework that can help dRs Snack in recording sales transactions in real-time, generate sales and financial reports quickly and accurately, improve operational efficiency and decision making. The method used for system development is Extreme Programing, where this method has a development target through the determination of unclear needs or changes to the needs very quickly and through a small to medium-sized team. The results of this study can manage menus and orders that have been proven to increase operational efficiency. The implementation of this system is able to reduce the time required for order processing and improve the accuracy of data related to stock and revenue. With an integrated system, customer service can be improved and reduce human error in summarizing total payments and ensure accuracy in payments. The system enables better data analysis, especially in monitoring order history and sales recap to improve sales reports. Suggestions from researchers to maximize the features of existing features and add features to complement the features that are already running.